Iron‐Promoted CC Bond Formation in the Gas Phase. Issue 48 (8th October 2015) - Troiani, Anna; Rosi, Marzio; Garzoli, Stefania; Salvitti, Chiara; de Petris, Giulia
Abstract: An unusual iron transfer and carbon–carbon coupling take place in gas‐phase ionized mixtures containing ferrocene and dichloromethane. Ferrous chloride and the protonated benzenium ion are eventually formed by a thermal and efficient reaction, through stable intermediates that undergo a remarkable reorganization. The mechanism of the concerted iron extrusion, carbon–chlorine bond activation and carbon–carbon bond formation is elucidated by electronic structure calculations that show the crucial role of iron. Abstract : Ion–molecule reactions : A remarkable reorganization occured in iron‐containing cations under ambient conditions. Fast and effective carbon–chlorine activation and carbon–carbon coupling was observed in gas‐phase mixtures containing ferrocene and dichloromethane, through reaction intermediates (see picture) that eventually extrude the iron giving ferrous chloride.